Avaliações física e funcional em pacientes oncológicos eletivos a cirurgias de médio e grande porte - Vieira Junior, Roberto Carlos (2022)
Current figures show that cancer is the first or second cause of premature death (between 30 and 69 years old) in 134 of 183 countries investigated. In addition, several complications and/or side effects are caused by cancer and its different treatment methods in any of the stages of diagnosis, affecting physical and functional capacity, promoting a decline in quality of life as well as a worsening in the prognosis of these patients. Objective: To assess physical and functional capacities as well as the prevalence of risk of sarcopenia, and to verify their association with sociodemographic variables, as well as their influence on the length of hospital stay in preoperative cancer patients.Materials and methods: All research protocols were submitted, appreciated and approved by the Research Ethics Committee of the Federal University of Mato Grosso (Process nº. 2.627.730). After the inclusion and exclusion criteria application, 169 patients composed the sample. Initially, patients were interviewed to collect sociodemographic information. Subsequently, physical and functional capacity assessments were carried out. The assessment of muscle mass was performed through two measurements of the circumference of the right calf using an inelastic and inextensible measuring tape. To assess muscle strength, the handgrip strength test was used with the aid of a hydraulic palmar dynamometer. For the assessment of physical performance, a four-meter gait speed test was applied. To assess the screening for sarcopenia, based on the patient's perception, the SARC-F questionnaire was applied. To identify the distribution of continuous data, the ShapiroWilk normality hypothesis test was used. When identifying that for most of the data the normal distribution could not be assumed, we performed the description of the continuous data of the patients through the median and the values of the 1st quartile and 3rd quartile (Q1 – Q3). For categorical variables, measures of absolute (n) and relative (%) frequencies were used. The Mantel-Haenszel chi-square test was used to analyze the associations between exposure and outcome of the different prevalence observed among the categories. Spearman's Rho (ρ) correlation test was used to verify possible correlations between the investigated variables. The established level of significance was p < 0.05, with a confidence of 95%. Results: Overall, 47.4% of patients had at least one risk associated with the development of sarcopenia, with 37.9% of patients having low muscle mass, 7.1% of patients having low muscle strength, and 6.5% of patients showed poor physical performance. Furthermore, 8.9% of the patients, evaluated using the SARC-F questionnaire, presented with possible sarcopenia. Furthermore, statistically significant associations were verified for: length of stay, with gender (p=0.038) and age group (p=0.029); muscle mass, with gender (p=0.014) and education (p=0.007); muscle strength with gender (p=0.010); physical performance with age group (p=0.027); risk of sarcopenia with sex (0.048) and education level (p=0.006). With regard to correlations, we observed a correlation between age and length of stay (ρ = 0.284; p< 0.001); age and physical performance (ρ = -0.269; p<0.001); length of stay and physical performance (ρ = -0.175; p = 0.023); length of stay and SARC-F (ρ = 0.184; p = 0.017); muscle strength and physical performance (ρ = 0.200; p = 0.009); muscle strength and SARC-F (ρ = -0.204; p = 0.008); and physical performance and SARC-F (ρ = -0.224; p = 0.003). Conclusion: Many patients had a reduction in physical and functional capacity as well as an increase in the prevalence of risk related to the diagnosis of sarcopenia. Therefore, this makes us reflect on the counseling and the need to assess patients regarding this problem, as early intervention, such as food supplementation and physical exercise, can favor a better postoperative prognosis, corresponding to a shorter hospital stay and greater survival and quality of life for the patient.